Pemberian Beberapa Jenis Biochar Terhadap C-Organik dan N-Total Pada Pertumbuhan Bibit Kelapa Sawit - Ingrid Ovie Yosephine; Sakiah Sakiah; Erpands Abdi Lestari Siahaan (Agrosains : Jurnal Penelitian Agronomi, 2020)
Vegetative growth response of palm oil DxP Dumpy variety using biochar rice husks, oil palm shells, corncobs and coconut shells in the Main Nursery, aims to determine the effect of the administration of several types of biochar on increasing C-organic and N-total in ultisol in the main nursery of oil palm plants. This research has been carried out at the Agricultural Agribusiness College of Agriculture Practices (STIPAP) Medan and soil analysis was carried out at the Asian Agri Laboratory, starting in March-August 2019. The method used was Randomized Group Design (RBD) non factorial with 3 replications, while the treatment factors used were B0 (NPK Compound), B1 Biochar Rice Husk (50 g/polybag), B2 Biochar Palm Oil Shell (50 g/polybag), B3 Biochar Corn Cobs (50 g/polybag), B4 Coconut Shell Biochar (50 g/polybag). The parameters observed were plant height (cm), girth (cm), number of leaves (strands), root wet weight (gr), root dry weight (gr) and pH, C-organik, and N-total soil. The results showed that the biochar treatment of rice husks, palm shells, corncobs and coconut shells had no significant effect on the observed parameters such as plant height, girth, number of leaves (strand, wet weight of roots and root dry weight, pH and N-total soil, but have a very significant effect on the increase in C-organic soil.